PHYSICIAN BURNOUT: WE NEED TO TREAT THE CAUSE NOT THE SYMPTOMS - Ullah, Tahmeed (Journal of Postgraduate Medical Institute, 2019)
A few years ago we were not very familiar with the terms like physician's burnout, work related quality of life and depression but in the last few years these terms have been increasingly recognized and published.Therefore, I selected this topic to highlight the problem of physician's burnout which we are facing as medical community in Pakistan. In literature we have a number of definitions of physician's burnout but the one I found enticing was that burnout is a prolonged and persistent stress reaction which is composed of a constellation of psychological symptoms of depersonalization, emotional instability, loss of personal identity and reduced personal efficacy. It is observed that physicians who are going through burnout typically exhibit anger, irritability, low self-esteem and decreased productivity. The other associated symptoms include progressive worsening of relations with patients, family members and colleagues. The most dreadful manifestation of physician burnout is suicide. The incidence of suicide is highest among the physicians and it is about 1.87 times more frequent in the health care professionals than the other members of the society2. As physicians we face stressful situations more frequently due to our profession because we are dealing with the most precious thing in anyone's life and that is their health. In our practice we don't have any chance of error or negligence2. The health care professionals are going through the agonies and pains of their patients.